2018
DOI: 10.1186/s12986-018-0293-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin D3 supplementation protects laying hens against lipopolysaccharide-induced immunological stress

Abstract: BackgroundThe effects of vitamin D on the immune function of laying hens are not well understood. This study investigated the effects of vitamin D3 (VD3) on laying performance and immunological functions in laying hens under Escherichia coli lipopolysaccharide (LPS) challenge.MethodsIn experiment one, 360 Jinghong-1 strain layers (32 weeks) were randomly divided into four groups with six replicates per group and 15 hens per replicate. Hens were fed a basal diet supplemented with different levels of VD3 (0; 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 84 publications
2
46
2
Order By: Relevance
“…The reason may contribute to that the content of vitamin D 3 (5000 IU) in diet had already met the layers' requirements in current study. It has been indicated that only when vitamin D 3 was deficient in the diet, the exogenous addition of vitamin D 3 or its analog can exert its improving effect on performance of laying hens ( Shen et al., 1981 , Goodson-Williams et al., 1986 , Geng et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason may contribute to that the content of vitamin D 3 (5000 IU) in diet had already met the layers' requirements in current study. It has been indicated that only when vitamin D 3 was deficient in the diet, the exogenous addition of vitamin D 3 or its analog can exert its improving effect on performance of laying hens ( Shen et al., 1981 , Goodson-Williams et al., 1986 , Geng et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hens housed under these conditions are not exposed to adequate natural light to transform 7-dihydrocholesterol at levels appropriate for the sufficient synthesis of VD 3 . Thus, VD 3 is usually added to layer feeds; these are critical for the homeostasis of calcium and to maintain laying performance, bone calcification, and eggshell formation ( 5 , 14 , 20 ). The biosynthesis of the active form 1, 25-dihydroxycholecalciferol (1,25-(OH) 2 D 3 ) from VD 3 was reviewed by Geng et al ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may have been a high bone index result in deterioration in shell quality [19]. In birds, the role of vitamin D 3 in Ca and P metabolism is crucial, due to its well-documented involvement in bone development and eggshell formation in laying hens [1]. Laying hens, during the later phase of the laying cycle, use Ca from their feed to maintain the hardness of their bones and to participate in the formation of the eggshell strength.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, artificial lighting has been widely used during the full phase of the laying cycle in confined laying hen houses. However, during the later phase of the laying cycle, laying hens in conventional cages are highly susceptible to osteoporosis, due to a calcium deficiency, which is accompanied by a decrease in production performance and egg quality and an increase in mortality [1]. It has been reported that ultraviolet (UV) light exposure could effectively improve the welfare and health of the birds [2][3][4], and be proved to be helpful for osteoporosis symptoms [5,6].…”
Section: Introductionmentioning
confidence: 99%